"A Thing is its Own Best Mask": Antagonisms of the Architectural Wrap. (28th November 2017) - Sterling, Colin
Abstract : This photo essay interrogates an increasingly familiar sight in the preservation landscape of our cities: buildings encased in images of themselves. The strange details of these architectural wraps are photographed as a means of exposing the surreal fissures that speak to their underlying ontologies, explored here with reference to Slavoj Zizek's concept of the parallax and Graham Harman's notion of immaterialism. This photographic archaeology further seeks to unravel the overarching inconsistencies of heritage and preservation, with the building wrap seen to embody many of the paradoxes and tensions of these fields.